BEVS - Blockchain Based E-Voting System - Nikhilesh Lalam, M.Shri Nithinn, Dr. R. Jebakumar, (International Journal of Advanced Science and Technology, 2020)
In this digital era, the current political scenario of many countries follows a democratic approach of appointing political leaders as respective heads of their Government, Voting is the chosen appropriate method of test in which each vote of a voter has unique value. Technology is being digitalized day by day, the election process methodology also needs an upgrade. The elections held nowadays, use a centralized system based on traditional ballot based system which is not as secure, reliant and robust as various encryption techniques, algorithms and security mechanisms such as Blockchain technology which has been adapted by projects like the Bitcoin, for online currency exchange. This paper is addresses the technological drawbacks existing and proposes a Blockchain based E-Voting System (BEVS), that involves a decentralized system and Blockchain technology is one of the solutions, using the same concept instead, for exchange of Votes as a standardized value. BEVS is an enhanced secure and transparent voting solution giving an ease of access for everyone at a lower cost.